Blood lactate clearance after maximal exercise depends on active recovery intensity - Devlin, J.; Paton, B.; Poole, L.; Sun, W.; Ferguson, C.; Wilson, J.; Kemi, O. J. (The Journal of Sports Medicine and Physical Fitness, 2014)
AIM: High-intensity exercise is time-limited by onset of fatigue, marked by accumulation of blood lactate. This is accentuated at maximal, all-out exercise that rapidly accumulates high blood lactate. The optimal active recovery intensity for clearing lactate after such maximal, all-out exercise remains unknown. Thus, we studied the intensity-dependence of lactate clearance during active recovery after maximal exercise. METHODS: We constructed a standardized maximal, all-out treadmill exercise protocol that predictably lead to voluntary exhaustion and blood lactate concentration>10 mM. Next, subjects ran series of all-out bouts that increased blood lactate concentration to 11.5±0.2 mM, followed by recovery exercises ranging 0% (passive)-100% of the lactate threshold. RESULTS: Repeated measurements showed faster lactate clearance during active versus passive recovery (P<0.01), and that active recovery at 60-100% of lactate threshold was more efficient for lactate clearance than lower intensity recovery (P<0.05). Active recovery at 80% of lactate threshold had the highest rate of and shortest time constant for lactate clearance (P<0.05), whereas the response during the other intensities was graded (100%=60%>40%>passive recovery, P<0.05). CONCLUSION: Active recovery after maximal all-out exercise clears accumulated blood lactate faster than passive recovery in an intensity-dependent manner, with maximum clearance occurring at active recovery of 80% of lactate threshold.